Optimalisasi layanan Anak Dalam Peningkatan Minat Baca Anak Pada Perpustakaan Proklamator Bung Hatta - Nofita Sari, Shinta; Rinaldo Marajar, Muhammad (UIN Imam Bonjol Padang, 2023)
This research was conducted at the children's service at the Bung Hatta Proclaimer Library, Bukittinggi. This research aims to find out what activities are carried out in children's services to increase children's interest in reading at the Proclaimer Bung Hatta Library, Bukittinggi. The research method used is descriptive qualitative, by making direct observations and conducting questions and answers with librarians at children's services. The results of this research state that the activities carried out in children's services at the Proclaimer Bung Hatta Library are 1) reading and writing activities, 2) activities to introduce Bung Hatta characters, 3) Library Tour activities, 4) Introduction to Traditional Games.